HPMA copolymer conjugated 5-aminolevulinic acid exhibits superior efficacy for photodynamic therapy with tumor-responsive and targeting properties - Islam, Rayhanul; Kotalík, Kevin; Šubr, Vladimír; Gao, Shanghui; Zhou, Jian-Rong; Yokomizo, Kazumi; Etrych, Tomáš; Fang, Jun (Nanomedicine, 2023)
In this study, we developed a nanoformulation of 5-aminolevulinic acid (5-ALA) for tumor-targeted photodynamic therapy, in which 5-ALA was conjugated with a biocompatible polymer N-(2-hydroxypropyl)methacrylamide (HPMA) through the hydrazone bond, i.e., P-ALA. P-ALA behaves as the nano-sized molecule with an average size of 5.5 nm in aqueous solution. P-ALA shows a largely increased release rate in acidic pH than physiological pH, suggesting the rapid release profile in acidic tumor environment. P-ALA did not show apparent cytotoxicity up to 0.1 mg/ml, however, under light irradiation, remarkable cell death was induced with the IC50 of 20-30 μg/ml. More importantly, we found significantly higher tumor accumulation of P-ALA than 5-ALA which benefit from its nano-size by taking advantage of the enhanced permeability and retention (EPR) effect. Consequently, P-ALA exhibited much improved in vivo antitumor efficacy without any apparent side effects. We thus anticipate the application of P-ALA as a nano-designed photosensitizer for anticancer photodynamic therapy.
Keywords: Aminolevulinic Acid; Humans; kyselina aminolevulová; EPR effect; doxorubicin; Antineoplastic Agents; Doxorubicin; lidé; fotochemoterapie; Photodynamic therapy; Tumor targeting; polymery; HPMA copolymer; Polymers; 5-Aminolevulinic acid; Neoplasms; nádorové buněčné linie; nádory; protinádorové látky; Photochemotherapy; Cell Line, Tumor